2013
DOI: 10.1590/s1806-83242013005000023
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between inflammatory infiltrate and epithelial lining in 214 cases of periapical cysts

Abstract: The aim of this study was to evaluate the prevalence of periapical cysts, identify their clinical and microscopic features and correlate their microscopic features with the inflammatory infiltrate present in the lesion site. A total of 214 cases were collected over a 10-year period. Clinical data, including gender, age, race, symptoms and location of the lesion, were recorded. Two independent examiners with no prior knowledge of the patients' clinical data conducted the microscopic evaluations. Statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…Moreover, host responses such as inflammation (4), angiogenesis (5), and, consequently, bone resorption (1) could modify the severity and prognoses of ICALs. Differential diagnosis among all ICALs is possible only with histopathological examination (6). Moreover, it was suggested that radiographic diagnosis of ICALs should not be used for scientific investigations (7).…”
mentioning
confidence: 99%
“…Moreover, host responses such as inflammation (4), angiogenesis (5), and, consequently, bone resorption (1) could modify the severity and prognoses of ICALs. Differential diagnosis among all ICALs is possible only with histopathological examination (6). Moreover, it was suggested that radiographic diagnosis of ICALs should not be used for scientific investigations (7).…”
mentioning
confidence: 99%
“…Scholl et al [23] reportan que el tratamiento de los quistes verdaderos consiste en: enucleación, resección radicular en caso de molares, marsupialización, tratamiento de conductos retrógrado o exodoncia del diente comprometido [23][24][25][26][27][28][29][30][31][32][33][34][35]. Las lesiones de quistes verdaderos son las que presentan menor probabilidad de resolverse mediante endodoncia convencional, puesto que están aisladas de los irritantes del canal radicular y son autosostenidas [74].…”
Section: Discussionunclassified
“…El 9% corresponde a quistes verdaderos, que disminuyen la probabilidad de eliminarse mediante tratamiento endodóntico convencional [7][8][9][10][11]29]. La mayor prevalencia de quiste radicular inflamatorio se presenta en mujeres y en edad adulta [21,33]. Algunos artículos reportan que no existe preferencia de edad ni sexo [6][7][8][9][10][11][12][13][14][15][16][17][18], mientras que otros autores reportan que esta lesión es más frecuente en el sexo masculino y que afecta la región anterior del maxilar [7-12, 22, 34, 35].…”
Section: Introductionunclassified
“…6,7 Several immune/inflammatory mediators and proteases may be involved in the formation of periapical granulomas and radicular cysts, such as transforming growth factor-β1 (TGF-β1) and matrix metalloproteinase-9 (MMP-9). 8,9 TGF-β1 is a polypeptide member of the transforming growth factor-β superfamily of cytokines, which is secreted by platelets and inflammatory cells. It performs many cellular functions, including the control of cell growth, cell proliferation, cell differentiation, apoptosis and inflammation, as well as tissue repair.…”
Section: Declaration Of Interestmentioning
confidence: 99%